2013
DOI: 10.1002/jmri.24697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of brown and white adipose tissues in infants and children with chemical‐shift‐encoded water‐fat MRI

Abstract: Purpose-To compare fat-signal fractions (FFs) and T 2 * values between brown (BAT) and white (WAT) adipose tissue located within the supraclavicular fossa and subcutaneous depots, respectively.Materials and Methods-Twelve infants and 39 children were studied. Children were divided into lean and overweight/obese sub-groups. Chemical-shift-encoded water-fat MRI was used to quantify FFs and T 2 * metrics in the supraclavicular and adjacent subcutaneous adipose tissue depots. Linear regression and t-tests were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 36 publications
5
39
0
Order By: Relevance
“…, and subcutaneous WAT ranges from 22 to 40 s Ϫ1 (30,31). The purpose of this research was to quantify the PET-CT and MRI characteristics of active and inactive clavicular BAT in healthy adult subjects and to compare these with the values in subcutaneous WAT.…”
mentioning
confidence: 99%
“…, and subcutaneous WAT ranges from 22 to 40 s Ϫ1 (30,31). The purpose of this research was to quantify the PET-CT and MRI characteristics of active and inactive clavicular BAT in healthy adult subjects and to compare these with the values in subcutaneous WAT.…”
mentioning
confidence: 99%
“…This results in a lower fat fraction in BAT compared to WAT. Thus, the most commonly used MRI methods to study BAT in humans are chemical shift-encoding based fat quantification techniques [44,45]. After consideration of the aforementioned confounding factors, chemical shift encodingbased fat quantification techniques can display the PDFF [22].…”
Section: Brown Adipose Tissuementioning
confidence: 99%
“…However, BAT can be depicted by either CT or MRI alone [36]. For MRI, BAT has been characterized by either water-fat imaging [37][38][39][40][41], T * 2 [38,42] or more novel approaches like Zero-Quantum Coherence [43,44]. The field is still in the early stages of mapping the true effects BAT has on the metabolism, and its association with metabolic disease.…”
Section: Brown Adipose Tissuementioning
confidence: 99%
“…The field is still in the early stages of mapping the true effects BAT has on the metabolism, and its association with metabolic disease. A range of smaller studies have shown metabolic associations, for instance Entringer et al observed that newborn with lower fat fraction in the supraclavicular BAT (sBAT) depot were leaner after 6 months [45], similarly Hu et al observed that sBAT was inversely associated with BMI during childhood [38], and Koksharova et al that BAT was associated with insulin sensitivity in adults [46].…”
Section: Brown Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation